Empowerment of Micro, Small and Medium Enterprises in Budo Tourism Village, North Minahasa Regency: Pemberdayaan Usaha Mikro Kecil Menengah Di Desa Wisata Budo Kabupaten Minahasa Utara - Onibala, Nancy; Kaparang, Vica; Putri, Anindya Puspita; Alhasni, Rahma A. (Universitas Lancang Kuning, 2025)
This Community Service activity is related to activities to encourage the development of local community entrepreneurship (MSMEs) to become a more attractive tourist destination for tourists to visit. This programme aims to increase the capacity of MSMEs in Budo Tourism Village through digital training for marketing and business management. This activity has helped MSME players in business management by creating a faster service system when someone orders culinary through one cashier door so that MSME players have the skills to present creative products. Ability in digital marketing, namely Partners have a website to market MSME products which include; culinary, crafts, and home stays. In its implementation, it uses an empowerment method with five stages, namely socialisation, training, technology application, mentoring and evaluation of activities, program sustainability. The results of community service were attended by 20 MSME members, and have fulfilled 2 levels of empowerment of target partners.